COMPANY VALUE ANALYSIS IN MANUFACTURING COMPANY (Emoft's Study on Manufacturing Company Registered on BEI 2013-2015 Period) - Riyadi, Syamsul (Jurnal Sinar Manajemen, 2018)
This study aims to determine the value of companies in the manufacturing sector consumer goods sector cosmetics subsector and household equipment. In this research the measuring instrument used to know the value of the company is measured using Tobin's Q ratio. This study uses a sample of manufacturing companies consumption sector cosmetic subsector and household purposes listed on the Indonesia Stock Exchange (BEI) from 2013 until 2015. Research It uses a quantitative descriptive method to analyze data. The results showed that the existence of companies that get the value of the company under one meaning that there are still companies that fall into the category of companies that are valued low (undervalued).Â